2008
DOI: 10.1007/s10562-008-9436-2
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrochlorination of Intermediates in the Production of Vinyl Chloride over Lanthanum Oxide-Based Catalysts

Abstract: Lanthanum oxide-based catalysts are active in the elimination of HCl from C 2 H 5 Cl, 1,2-C 2 H 4 Cl 2 and 1,1,2-C 2 H 3 Cl 3 leading to the formation of their respective chlorinated ethenes. An oxygen-rich catalytic surface may form CO, CO 2 and C 2 HCl as side products, whereas with chlorine-rich catalytic surfaces a stable product distribution is achieved with 100% selectivity towards the formation of ethenes, such as the valuable C 2 H 3 Cl intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…The chemistry of gas‐phase β‐elimination over solid catalysts has been well established on alkyl halides (RX) with different α‐leaving groups and/or β‐substituents . However, there were few academic articles on the selective dehydrohalogenation of haloalkanes with more than one halogen leaving groups on the same C α atom.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of gas‐phase β‐elimination over solid catalysts has been well established on alkyl halides (RX) with different α‐leaving groups and/or β‐substituents . However, there were few academic articles on the selective dehydrohalogenation of haloalkanes with more than one halogen leaving groups on the same C α atom.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxychlorination cycle can be skipped, once terminal lattice oxygen is formed via condensation via the hydrolysis of surface hydroxyl groups (arrow 5). 37 The catalytic destruction of CMs over terminal lattice oxygen of La is well described, 38 and it is hypothesized that a similar mechanism plays a role for the lanthanide-based catalysts tested in this study. When the CM catalytically destructs (arrows 6−7), surface chlorination is again obtained, where it crosses paths with the oxychlorination cycle again.…”
Section: Experimental Methodsmentioning
confidence: 74%
“…Various catalysts for DCE conversion to VCM have been studied, e.g., metal oxides and chlorides, and molecular sieves, to enable DCE pyrolysis at 300-400 • C, but the catalysts were rapidly deactivated and unsuitable for industry [5][6][7][8][9][10][11][12]. Yozo and co-workers first reported that a polyacrylonitrile-based active carbon fiber could catalyze dehydrochlorination of DCE into VCM over 300 • C, but catalytic activity fast decreased [13].…”
Section: Introductionmentioning
confidence: 99%